Diclofenac--Acetaminophen Combination Induced Acute Kidney Injury In Postoperative Pain Relief - Yan Zhu; Ping Xu; Qing Wang; Jian-quan Luo; Yi-wen Xiao; Yi-yi Li; Yan-gang Zhou; Andrew Cave; Hoan Linh Banh (Frontiers Media S.A., 2018)
Purpose: The objective of this study was to determine: 1) the incidence and the risk factors of diclofenac/acetaminophen combination as a single agent induced Acute Kidney Injury (AKI) in postoperative pain relief 2) the average cost and length of hospital stay for patients in AKI group and non-AKI group. Methods: All patients with no prior history of chronic kidney disease (CKD) and normal serum creatinine [44~130 μmol /l] who received diclofenac and acetaminophen combination as a single agent intramuscularly (IM) between January and December 2015 in The Second Xiangya Hospital, Changsha, Hunan, China were included in this retrospective own-control study. Baseline serum creatinine (SCr) and SCr during NSAID use were collected. AKI is defined as an increased of Scr over 1.5 times the baseline. Multivariate analyses were performed with a logistic regression model to assess the significant risk factors of AKI. Results: A total of 821 patients were included in the study with 63 [7.7%] patients had diclofenac/acetaminophen combination single agent induced AKI. Multivariate analysis confirmed that using diclofenac/acetaminophen combination after surgeries within 24 h were significantly associated with AKI [odds ratio, OR, 2.173; 95% CI, 1.113-4.243; P=0.023]. The average cost and length of hospitalization in AKI group was 1.87 times [p=0.000] and 1.2 times [p=0.043] comparison than non-AKI group, respectively. Conclusions: The incidence of diclofenac/acetaminophen combination single agent induced AKI in postoperative pain relief was 7.7%. Patients with hypertension or liver cirrhosis was more likely to develop AKI and using diclofenac/acetaminophen combination after surgeries within 24 h was significant risk factors for AKI. AKI prolonged the cost and length of hospitalization.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.